Pre-nucleation geochemical heterogeneity within glassy anatectic inclusions and the role of water in glass preservation - Tacchetto, Tom; Reddy, Steven; Bartoli, O.; Rickard, William; Fougerouse, Denis; Saxey, David; Quadir, Z.; Clark, Chris (SPRINGER, 2021)
Glassy melt inclusions are unique geological repositories that preserve evidence of the formation and evolution of mantle and crustal-derived magmas. However, the mechanisms responsible for their preservation in slowly cooled crustal rocks remain contentious, in some part due to their small size (commonly < 10 µm) and the technical difficulty in quantifying composition and microstructures. In this work, time-of-flight secondary ion mass spectrometry, transmission electron microscopy and atom probe tomography are used to characterize glassy melt inclusions found in peritectic garnets of a migmatite from the Spanish Betic Cordillera. The glassy melt inclusions coexist in a close spatial relationship with partially to totally crystallized melt inclusions (nanogranitoids). Analyses of the glassy inclusions show a heterogeneous, patchy distribution of Na and K within the glass and along inclusion walls. Nanoscale spherical domains of Al, Fe, K, Na, Cl and Li are also found systematically distributed at inclusion edges, and are interpreted to represent pre-nucleation clusters. The location and compositional similarity of these clusters with micas and feldspars in nanogranitoids indicate that the glassy inclusions represent former nanogranitoids “captured” at an earlier stage of crystallization, suggesting a likely common origin for both the glassy inclusions and nanogranitoids. A comparison between the composition of melt inclusions with previously published data reveals that preserved glassy inclusions contain significant less H2O (av. 2.72 wt%) than nanogranitoids (average of 6.91 wt%). This suggests the low-H2O content representing a further impediment to crystallization, along with the very small volume of these cavities, favouring the coexistence of glassy inclusions and nanogranitoids. In contrast, crystal nucleation is enhanced in more hydrous melts, where H2O reduces melt viscosity and promotes diffusion.